RELEVANCE OF INTEGRATION OF SUSTAINABILITY ISSUES IN CORPORATE INVESTMENT AND FINANCE STRATEGIES: THEORY AND PRACTICE - Svechnikova, S.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Issues of sustainable development of economic entities are widely discussed in the scientific and business community. Issues of sustainable development are particularly widely discussed in the context of investment activities: for example, in the last decade, the concept of responsible investment has become increasingly relevant - an approach that takes into account environmental, social and corporate governance factors in order to minimize risks, ensure a sustainable return on investment, and improve the quality of the portfolio in the process of making investment decisions, primarily in the long term. Despite the high degree of theoretical elaboration of issues of integration of sustainable development aspects, in practice, the full integration of sustainable development priorities in the activities of companies is hindered by a number of factors, including the heterogeneity of the methodological base and insufficient coverage of successful examples of integration of sustainable development aspects in open sources. When investigating the impact of integrating sustainable development aspects into a company's investment and financial strategy, representatives of both the scientific and professional communities tend to focus on finding a relationship between the integration of sustainable development factors and the results of the company's activities in the area that is the object of research. This article analyzes and synthesizes the results of research on the impact of integrating sustainable development priorities in the company's investment and financial strategies on the results of its activities in various areas. The article discusses the problems that prevent the full integration of sustainable development aspects, as well as provides methodological recommendations and approaches used in business practice to integrate the factors of sustainable development.